The Effectiveness of Deep Breathing Relaxation in Reducing Acute Pain Intensity Among Patients With Urinary Tract Infection (UTI): A Nursing Care Evaluation (PT. LARPA JAYA PUBLISHER, 2024)
Urinary Tract Infection (UTI) is a condition where the urinary tract is infected by pathogens, resulting in the presence of bacteria in the urine produced. The Indonesian Ministry of Health estimates that there are 90-100 cases of UTI per 100,000 population per year, or approximately 180,000 new cases per year. The incidence of UTI can be influenced by various factors, such as gender, age, urinary retention habits, genital hygiene, behavior, and kidney stone disease.: To provide nursing care to clients with Urinary Tract Infections with acute pain problems to reduce complaints and improve comfort. This is a case study using a nursing process approach, including assessment, diagnosis, intervention, implementation, and evaluation. Data were collected through interviews, observations, and physical examinations, at the Regional General Hospital. The assessment showed abdominal pain and headache (scale 5/10), nausea, and decreased appetite. The main interventions included pain management (non-pharmacological therapy and deep breathing therapy), dietary education, and medication administration according to collaboration. Evaluation after 24 hours showed a decrease in pain (scale 2/10) and an increase in nutritional intake. Nursing care based on pain management and education is effective in reducing symptoms of Urinary Tract Infections. Long-term monitoring is necessary to prevent recurrence.